Social Media Influencers as a Marketing Strategy for Islamic Banking: A Study on Generation Z Consumers - Sri Ayu Wahadaniyah (Multidisciplinary Journal of Contemporary Islamic Discourse, 2026)
This research is motivated by the rapid development of digital technology, which significantly influences social dynamics. Various content across platforms is now easily shared, making it more convenient for the public to access information, engage in communication, and conduct buying and selling activities. The objective of this study is to explore the implementation of social media influencers in increasing the purchase intention of Generation Z, specifically individuals aged 18 to 24, in using Islamic banking products. The novelty of this study lies in its focus on the intersection between Islamic finance marketing and digital influencer strategy within the behavior of digitally native youth. A qualitative research method is employed to gain a deep, detailed, and comprehensive understanding of this social phenomenon. Data collection is conducted through interviews and supported by questionnaire-based surveys. The findings reveal that marketing strategies involving social media influencers are relatively effective in shaping purchase intention. However, the study also highlights that the creativity and relevance of content still require improvement to better capture the interest and trust of the target audience. The presence and credibility of influencers play a crucial role in the success of these strategies, as engaging and authentic content strongly impacts Generation Z's perception and decision-making. This research implies that Islamic banking institutions must continue to innovate in content development and select influencers who align with their brand values to enhance marketing effectiveness among young Muslim consumers.